Characterization of carbon nanotube aluminium nano composite- effect of ball milling time on particle size - Abdullah, Umma; Maleque, Md. Abdul; Yaacob, Iskandar Idris; Ali, Mohammad Yeakub ("International Journal of Academic Research" (IJAR-Azerbaijan), 2013)
The discoveries of carbon nano tube change the direction of the research in the field of fibrous materials and are attracting much interest as reinforcement to aluminium matrix for carbon nano tubes (CNTs) aluminium (Al) matrix nano-composite. This is due to unique properties such as high strength, elastic modulus, flexibility and high aspect ratios. However, the quality of the dispersion is the major concerning factor which determines the homogeneity of the enhanced mechanical and tribological properties of the composite. This work study the particle size of aluminium powder in the CNTs-Al nano-composite prepared with different weight percentage of CNT in aluminium matrix using powder metallurgy route under high energy planetary ball milling operations at different time intervals. The experimental results showed homogeneous dispersion of CNTs in aluminium matrix at 250 rpm and the aluminium particle size increased from 78 μm up to 156 μm after just 3 hrs of milling. The preliminary mixing of CNTs and aluminium powder in a tube via manual shaking and the speed used could be the main contributing factor in achieving uniform dispersion of CNT in aluminium matrix within short time.